1998
DOI: 10.1046/j.1365-2141.1998.00663.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray ionization mass spectrometry identification of fibrinogen Banks Peninsula (γ280Tyr→Cys): a new variant with defective polymerization

Abstract: Summary. Fibrinogen Banks Peninsula was identified in the mother of a patient referred for investigation following recurrent epistaxis. Coagulation tests revealed prolonged thrombin and reptilase times and a decreased functional fibrinogen level. Thrombin-catalysed release of fibrinopeptides A and B was normal, and no abnormalities were detected by DNA sequencing of the regions encoding the thrombin cleavage sites in the Aa and Bb genes. Reducing SDS-PAGE and reverse-phase HPLC analysis of purified fibrinogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 33 publications
(44 reference statements)
1
27
0
Order By: Relevance
“…Interestingly, each vArg-275 residue in the DD fragment has a different set of contacts, i.e., with vTyr-280 in one direction and with vSer-300 in the other. To support this finding, a V Tyr-280 to Cys substitution has been reported in association with defective fibrin polymerization in fibrinogen Banks Peninsula [52]. Impaired D:D association may also take place in variant fibrinogens with a mutation located close to these residues, including vGly-268 to Glu (Kurashiki I) [53], vAsn-308 to Lys (Kyoto land others) [54] or to lie (Baltimore III) [55], and vMet-310 to Thr (Asahi) [56].…”
Section: Alteration In the A Site (The A-chain Knob)mentioning
confidence: 90%
“…Interestingly, each vArg-275 residue in the DD fragment has a different set of contacts, i.e., with vTyr-280 in one direction and with vSer-300 in the other. To support this finding, a V Tyr-280 to Cys substitution has been reported in association with defective fibrin polymerization in fibrinogen Banks Peninsula [52]. Impaired D:D association may also take place in variant fibrinogens with a mutation located close to these residues, including vGly-268 to Glu (Kurashiki I) [53], vAsn-308 to Lys (Kyoto land others) [54] or to lie (Baltimore III) [55], and vMet-310 to Thr (Asahi) [56].…”
Section: Alteration In the A Site (The A-chain Knob)mentioning
confidence: 90%
“…We present a novel PCR/restriction digestion assay for the dection of the new Á280Tyr→Cys mutation of fibrinogen recently described by Fellowes et al [3], which is associated with mild bleeding [5], although it does not appear to cause severe disease. Unfortunately, no samples from patients with this defect were available.…”
Section: Discussionmentioning
confidence: 99%
“…During the final stage of the coagulation cascade fibrinogen is converted to an active form by thrombin-mediated cleavage of small peptides. A large number of familial dysfibrinogenemias have been described so far [1,2], and Fellowes et al [3] recently found a new mutation of Tyr→ Cys at position 280 of the Á chain of fibrinogen to cause fibrinogen Banks peninsula. Electrospray ionization mass spectrometry was used to identify this mutation and the genetic basis was verified by polymerase chain reaction (PCR), amplifying and sequencing exon 8 of the Á chain.…”
Section: Introductionmentioning
confidence: 99%
“…The mature 340 kDa protein is a dimer of three polypeptide chains (Aa Bb c) 2 arranged in a linear D-E-D structure. The central E domain, formed from the N-termini of all six chains, is connected to the globular D domains by a coiled coil of all three chains.…”
mentioning
confidence: 99%
“…It can arise from either gene mutation [2] or post-translational events [3]. The congenital condition can be precipitated by polymorphisms or personal mutations, and acquired changes can be caused by liver disease [4] or drug-induced epigenetic events [5].…”
mentioning
confidence: 99%